2011
DOI: 10.1128/aac.01350-10
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Candida sp. fks Hot Spot Mutants by Using the Method of the CLSI M27-A3 Document with the Addition of Bovine Serum Albumin

Abstract: Echinocandins are highly bound to serum proteins, altering their antifungal properties. The addition of 50% human serum to the MIC assay improves the identification of echinocandin-resistant Candida spp. harboring fks hot spot mutations. However, this modification cannot readily be applied to the method of the CLSI M27-A3 document due to safety and standardization difficulties. The aim of this study was to evaluate commercial bovine serum albumin (BSA) as a safe and standardized alternative to human serum. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…The decreased growth of our WT C. glabrata isolates in 50% serum is consistent with a previous report (Garcia-Effron et al, 2011), and the low in vivo growth rate suggests a relatively low virulence. Considering this, the extremely weak elimination capacity of the treatments was even more notable.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…The decreased growth of our WT C. glabrata isolates in 50% serum is consistent with a previous report (Garcia-Effron et al, 2011), and the low in vivo growth rate suggests a relatively low virulence. Considering this, the extremely weak elimination capacity of the treatments was even more notable.…”
supporting
confidence: 79%
“…MICs of caspofungin (Sigma) in RPMI 1640 and in RPMI 1640 supplemented with 50% serum (hereafter referred to as 50% serum) (human serum from a male, type AB; Sigma) were determined simultaneously using the standard CLSI (2008) broth macrodilution method (Földi et al, 2012a, b;Garcia-Effron et al, 2011;Szilágyi et al, 2012). The caspofungin final concentration ranged between 0.03 and 32 mg l 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies (4,12) have demonstrated that addition of bovine serum albumin to the medium increased the power of discrimination between wild-type and mutant isolates. It has also been suggested that the potency of these drugs may be affected by the solvent, given their relatively hydrophobic character.…”
mentioning
confidence: 99%
“…In order to get mechanistic insight on the interaction of serum with caspofungin, we focused on albumin, the major serum protein component that binds highly to caspofungin (1,32,33). Indeed, we found that the positive interaction of serum with caspofungin was mediated almost exclusively by albumin.…”
Section: Discussionmentioning
confidence: 99%